Objects in the Archives : Modern Material Culture and Heritage in the North - Mímisson, Kristján (Taylor & Francis, 2025)
Situated on an intersection between Material Culture Studies, History and Museum and Archival Studies, this book investigates the material world of the Icelandic population in the late Modern Era. Utilizing the great wealth of inventories of household goods stored at The National Archives of Iceland in conjunction with material objects, the book highlights new paths and insights into understanding people’s possessions and material relations, and the entwined biographies of people and things. It shows how people shaped their own lives by means of things and how these material relations are “archived” and represented in heritage and museum spaces. The book is divided into two parts that explore how material culture contributes to history, the relationship between things and text, and the practice of collecting things and address the process of assembly, or how things gather. Micro and macro methods of investigation tease out new approaches to debates around human–thing relationships, acknowledging ideas about material agency and social significance and that the human–material relation is reciprocal. This volume will appeal to students and researchers within the field of archaeology, material culture studies, museum studies, heritage, and the history of material culture.